The effect of task complexity and gender differences on EFL learners’ writing performance - Mohammad, Mahgoub Kamel Mahmoud; Nik Aloesnita, Nik Mohd Alwi (World Journal of Advanced Research and Reviews (WJARR), 2023)
The current study investigates the Effect of Task Complexity and Gender Differences on EFL Learners’ Writing Performance. Task complexity is the inherent cognitive demands of the tasks imposed on the learners by the structure of the tasks. It is investigated along the resource-dispersing variables of pre-task planning time, post-task editing time and prior knowledge. This study also tries to intertwine the concepts of task complexity and sociolinguistics (i.e., gender differences). The participants are 160 high school students (80 males and 80 females) studying at international schools in Riyadh City, Saudi Arabia. The writing topics were selected among the essay prompts similar to those of the IELTS test using the cause-and-effect essay task type. A series of T-Test and one-way ANOVAs were used for detecting the significant differences within the same gender and across genders, Cronbach's alpha (α) for the task reliability, Wilk’s Lambda for variable contributions, Partial Eta squared (ηp2) for the effect size, and the Observed Power (or post-hoc power) for the test statistical power. This study is thought to be laden with manifold implications for varied stakeholders within the realm of didactics, including language teachers, learners, syllabus designers, test developers, educational bodies and many other individuals in the ministries of education and higher education. Should this be done, it can contribute to improving EFL undergraduate students’ ability to a level of writing production that is more likely to be satisfactory. The current study found different effects of task complexity on EFL learners’ writing performance across gender. There were both similar and different impacts on CAF metrics between the writing tasks across genders. The results indicate a partial support to the predictions of Skehan and Foster (2001) and those of Robinson (2005) where there is a partial increase in the CAF scores along the resource-dispersing variables. Conversely, findings show no support to the Gender Similarities Hypothesis (GSH) by J. S. Hyde (2005). This study also explored the effect percentage of task complexity along the resource dispersing variables planning time, editing time and prior knowledge on CAF. Besides, the researcher sorted the significant CAF metrics within same gender and across genders according to their occurrence and percentage in the performance of the current student participants.It is recommended that pedagogical tasks should be sequenced for learners on the basis of increasing in their cognitive complexity to help promote learners' performance in terms of accuracy, fluency, and complexity. In addition, educators should motivate male students to engage more and perform better in the writing classes; syllabus designers should introduce new teaching methodologies that help bridge the gap in gender differences between boys and girls.